FACTORS ASSOCIATED WITH POST-STROKE SHOULDER PAIN AMONG PATIENTS TREATED AT THE REHABILITATION CENTER OF BACH MAI HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with the severity of post-stroke shoulder pain among patients treated at the Rehabilitation Center of Bach Mai Hospital in 2023.Methods: A cross-sectional descriptive study was conducted on 33 patients with post-stroke shoulder pain from February to May 2023. Shoulder pain severity was assessed using the VAS. Associated factors included age, sex, stroke type, shoulder subluxation/dislocation, proprioceptive impairment, Brunnstrom upper-limb recovery stage, Barthel Index, and shoulder tendon-muscle injuries. Data were analyzed using Fisher’s exact test and Spearman’s correlation coefficient.Results: Shoulder pain severity was significantly associated with shoulder subluxation/dislocation (p = 0,009) and proprioceptive impairment (rₛ = 0,364; p = 0,037). Pain severity was negatively correlated with Brunnstrom recovery stages (rₛ = -0.447; p = 0.009) and Barthel Index scores (rₛ = -0,583; p < 0,001). No significant associations were found between pain severity and age, sex, stroke type, or shoulder tendon-muscle injuries (p > 0,05).Conclusion: Post-stroke shoulder pain severity was associated with shoulder subluxation/dislocation and proprioceptive impairment. It was also negatively correlated with upper-limb motor recovery and activities of daily living.
Keywords: Post-stroke shoulder pain, stroke, rehabilitation, associated factors.